The effects of hesperidin or naringin dietary supplementation on the milk properties of dairy ewes. (16th August 2019) - Simitzis, Panagiotis; Massouras, Theofilos; Goliomytis, Michael; Charismiadou, Maria; Moschou, Katerina; Economou, Christina; Papadedes, Vagelis; Lepesioti, Sofia; Deligeorgis, Stelios
Abstract: BACKGROUND: Fortification of animal products with natural bioactive compounds appears to improve their quality and protects consumers against oxidation effects. An experiment was therefore conducted to examine the effects of hesperidin or naringin on milk oxidative stability, yield, composition, coagulation properties, and the fatty acid profile in dairy sheep. Thirty‐six Chios ewes were assigned to four groups. A control group was fed a concentrate diet without supplementation. The other three groups were provided with the same diet further supplemented with hesperidin (6000 mg kg −1 ), naringin (6000 mg kg −1 ), or α ‐tocopheryl acetate (200 mg kg −1 ). The efficacy of flavonoids after a change in diet composition that lowered milk oxidation values by itself was also tested. The duration of the experiment was 28 days with alfalfa hay being the only forage source for the first 14 days, whereas after the 15th day a mixture of alfalfa hay and wheat straw (65:35) was provided. RESULTS: The oxidative stability of milk was improved after 14 days of addition of the examined flavonoids ( P < 0.05). Milk malondialdehyde (MDA) values were also decreased as a result of flavonoid dietary supplementation, 14 days after the modification of the forage source. On the other hand, no significant differences in yield, chemical composition, coagulation properties, and fatty acid profile of ewe milk were observed among the treatments throughout the experiment. CONCLUSION: Enrichment of dairy ewes' diets with hesperidin and naringin might be effective in improving milk's oxidative stability without any effects on the milk's chemical composition, coagulation properties, and fatty acid profile. © 2019 Society of Chemical Industry